Model Pembelajaran Learning Cycle 7E: Suatu Eksperimentasi Pada Pembelajaran Matematika Materi Aritmetika Sosial di Kelas VII - Ebennejer Gea; Sylvia J.A Sumarauw; Helen Y. Angmalisang (Departement of Mathematics Education, 2024)
The mathematics learning outcomes of students at SMPN 3 Tondano are still meagre due to students' lack of basic mathematics skills, motivation and interest in students' mathematics learning in the learning process, so the presentation of completeness is only 40%. An alternative to overcome this problem is to use the 7E learning cycle learning model. This research examines the influence of the Learning Cycle 7E learning model on students' mathematics learning outcomes in class VII social arithmetic material at SMPN 3 Tondano for the 2023/2024 academic year. The subjects in the research were 43 students consisting of 2 classes, namely class VII-A with a total of 23 students and class VII-B with a total of 22 students. This type of research is a quasi-experiment with a quantitative approach. The data analysis used was the normality, homogeneity, and hypothesis tests. The instrument in this research is a written test in the form of a description. The results of the research showed that the average learning outcomes of experimental class students were 81.90 and control class 74.08, while the t-test calculation results obtained tcount = 3.843318 and compared with the ttable value = 2.01669 with a significance level of 5%. These results show that tcount > ttable, so that H0 is rejected. So, the 7E learning cycle model influences the mathematics learning outcomes of class VII students at SMPN 3 Tondano.